2016
DOI: 10.1021/acs.analchem.6b03395
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Nano-ESI Atmospheric-Pressure Ion Mobility Mass Spectrometry with Enhanced Ion Sampling

Abstract: Ion mobility-mass spectrometry (IM-MS) has gained considerable attention for detection of clusters and weakly bound species created by electrospray ionization (ESI). Atmospheric-pressure (AP) IM-MS offers an advantage in these studies compared to its low-pressure counterpart, owing to soft introduction of ions into the mobility cell with minimal ion activation. Here, we report new approaches to improve the sensitivity and soft ion introduction in AP-IM-MS. For the former, we demonstrate enhanced aerodynamic sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 30 publications
(51 reference statements)
0
21
0
Order By: Relevance
“…Stadlmair et al 17 used nano‐ESI to detect the degradation products of different enzymes in water. McMahon et al 18,19 combined pulsed nano‐ESI with ion mobility mass spectrometry to improve the efficiency of ion acquisition. Microextraction by packed sorbent (MEPS) 20,21 is one of the fastest developed microextraction sample processing technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Stadlmair et al 17 used nano‐ESI to detect the degradation products of different enzymes in water. McMahon et al 18,19 combined pulsed nano‐ESI with ion mobility mass spectrometry to improve the efficiency of ion acquisition. Microextraction by packed sorbent (MEPS) 20,21 is one of the fastest developed microextraction sample processing technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Low duty cycles in AP drift tubes, however, lead to reduced sensitivity and low sample utilization efficiency. Multiplexing methodologies have been developed to improve sensitivity. In parallel, we have explored a different strategy using pulsed nano-ESI for ion introduction into the IM cell . In this approach, the pulsed spray replaces the entrance gate of the IM cell and serves as both the ion source and ion injection method.…”
Section: Introductionmentioning
confidence: 99%
“…Various pulsing schemes have been utilized such as a piezoelectric-assisted pulsing, 6 induced pulsing through a dielectric, [7][8][9] pulsing the potential supplied to the solution, [10][11][12][13] and pulsing the electric field in the proximity of the emitter. 14,15 Practical and fundamental advantages have been demonstrated for pulsed nano-ESI relative to continuous operation. For example, several studies have shown reduced sample consumption in pulsed mode relative to continuous operation.…”
Section: Introductionmentioning
confidence: 99%
“…12 Controlled pulsing of nano-ESI and short ion bursts also enable the direct use of this ionization mode for introducing discrete packets of ions into drift tubes utilized in atmospheric-pressure (AP) ion mobility separations. 14,15 In a recent study using this approach, we investigated the effect of nano-ESI pulse duration on ionization, demonstrating that long pulse duration preferentially enhanced the intensity of low-ionization-efficiency analytes, while the collision cross sections did not change appreciably. These studies indicated a temporal evolution of droplet sizes during a pulsed spray and suggested that final ion structures emerge rapidly with minimal impact of pulse duration on the measured collision cross section.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation